2021
DOI: 10.1007/s12144-021-01674-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on mental health and health-related quality of life among university students in Turkey

Abstract: The COVID-19 health crisis has reached pandemic scale spreading globally. The present study examines the COVID-19 pandemic's impact on psychological and physical health-related quality of life (HRQOL) among university students in Turkey. A cross-sectional survey design was used for data collection. From May 11th to May 15th 2020, the study utilized snowball sampling techniques to gather data through an online survey. The pandemic's psychological effects on participants were measured by the Impact of Event Scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
6
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 38 publications
5
41
6
2
Order By: Relevance
“…This study reveals that the prevalence of depression was consistent with a study done in Italy (27.8%) (Marelli et al, 2020), North Carolina, Taiwan (31.7%) (Fruehwirth et al, 2021), and the United States of America (31.2%) (Batra et al, 2021); but higher than the study done in Bench Sheko zone, Southwest, Ethiopia (21.1%) (Mekonen et al, 2020), and lower than the study done in Italy (72.93%), Turkey (64.6%) (Ayyildiz et al, 2021), Bangladesh (46.9%) (Hasan et al, 2020), Bangladeshi (72%) (Faisal et al, 2021), the United States of America (44%) (Son et al, 2020), Egypt (53.6%) (Ghazawy et al, 2020), Hong Kong (84.7%) (Lai et al, 2020), Gonder, Ethiopia (40.2%) (Ali & Muluneh, 2021) and Addis Ababa, Ethiopia (51%) (Sahile et al, 2020). The mild levels of depression were 19.2%, which were similar to studies done in Addis Ababa, Ethiopia (18.1%) (Sahile et al, 2020), and Turkey (16.0%) (Ayyildiz et al, 2021). The moderate and severe levels of depression were 10.6% and 0.3%, respectively, which was lower than the study done in Addis Ababa, Ethiopia, 20.9% moderate, 7.2% severe, and 4.6% extremely severe (Sahile et al, 2020) and Turkey, which revealed 26.8% moderate and 10.7% severe (Ayyildiz et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study reveals that the prevalence of depression was consistent with a study done in Italy (27.8%) (Marelli et al, 2020), North Carolina, Taiwan (31.7%) (Fruehwirth et al, 2021), and the United States of America (31.2%) (Batra et al, 2021); but higher than the study done in Bench Sheko zone, Southwest, Ethiopia (21.1%) (Mekonen et al, 2020), and lower than the study done in Italy (72.93%), Turkey (64.6%) (Ayyildiz et al, 2021), Bangladesh (46.9%) (Hasan et al, 2020), Bangladeshi (72%) (Faisal et al, 2021), the United States of America (44%) (Son et al, 2020), Egypt (53.6%) (Ghazawy et al, 2020), Hong Kong (84.7%) (Lai et al, 2020), Gonder, Ethiopia (40.2%) (Ali & Muluneh, 2021) and Addis Ababa, Ethiopia (51%) (Sahile et al, 2020). The mild levels of depression were 19.2%, which were similar to studies done in Addis Ababa, Ethiopia (18.1%) (Sahile et al, 2020), and Turkey (16.0%) (Ayyildiz et al, 2021). The moderate and severe levels of depression were 10.6% and 0.3%, respectively, which was lower than the study done in Addis Ababa, Ethiopia, 20.9% moderate, 7.2% severe, and 4.6% extremely severe (Sahile et al, 2020) and Turkey, which revealed 26.8% moderate and 10.7% severe (Ayyildiz et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…Mild level of anxiety (17.3%) was higher than a study done in Addis Ababa, Ethiopia 11.1% (Sahile et al, 2020), Turkey11.1% (Ayyildiz et al, 2021), and Malaysia 20.4% (Sundarasen et al, 2020) and moderate (14.6%), severe (2.8%), and extremely severe (0.3%) level of anxiety was lower than the study done Ethiopia; 20.9% moderate, 6.5% severe, and 13.1% extremely severe (Sahile et al, 2020), Turkey; 20.3% moderate, 6.8% severe 10.4%, and extremely severe 10.4% (Ayyildiz et al, 2021), Malaysia; 6.6% severe, and 2.8% extremely severe (Sundarasen et al, 2020) and China, 21.3% mild anxiety (Cao et al, 2020).…”
Section: Discussioncontrasting
confidence: 57%
“…Regarding stress, the result of the surveyed students was higher than those of undergraduates from Bangladesh [ 28 ], Egypt [ 26 ], Ethiopia [ 24 , 30 ], Lebanon [ 25 ] and Turkey [ 29 ], whose percentages ranged from 12.7% to 47.8%. For anxiety, the percentage was lower than those in Egypt (53.6%) and higher than the others (27.7% to 48.6%).…”
Section: Discussionmentioning
confidence: 99%
“…A review study before the pandemic identified that female gender was among the sociodemographic characteristics most associated with psychological distress in undergraduates [ 12 ]. During the pandemic, this variable was associated with symptoms of depression, anxiety and stress in several studies in students [ 24 , 26 , 27 , 29 ] and in populations in Brazil [ 7 10 ] and other countries [ 5 , 67 , 68 ]. Such a condition points to the need for further studies aiming to identify possible common causes of female susceptibility to stress during a pandemic crisis, regardless of age and culture.…”
Section: Discussionmentioning
confidence: 99%
“…Structured clinical interviews and functional neuroimaging are the gold standard for establishing a psychiatric diagnosis. 45 Despite these limitations, this study was able to report anxiety and depression among the general population during the COVID-19 pandemic, however, the previous psychological conditions of the study participants before the pandemic could not be assessed and cannot be reported.…”
Section: Limitationsmentioning
confidence: 89%